2014
DOI: 10.1002/maco.201307528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corrosion behavior of Mg-1.5Zn-0.6Zr and AZ91D alloys in a NaCl solution

Abstract: The microstructure and corrosion behavior of as-cast Mg-1.5Zn-0.6Zr alloy and a comparative AZ91D alloy were investigated through metallographic observations, X-ray diffraction, electron probe micro-analysis, immersion tests, and cyclic polarization measurements. The Mg-1.5Zn-0.6Zr exhibited a singlephase solid solution characteristic and had fine equiaxed grains, while the AZ91D consisted of a-Mg matrix and b-Mg 17 Al 12 second phases. It was found that Zr is enriched in the center of most grains in Mg-1.5Zn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
1
12
0
2
Order By: Relevance
“…After 2 days, AZ91 was corroded on some parts of its surface and its material loss increased gradually as shown in figure 5.7. The corrosion morphology of AZ91 in 3.5% NaCl was similar to the morphology caused by 5% NaCl reported in [147]. Raman et al [30] described that the die cast AZ91D showed a steady decrease in corrosion rate up to 6 days, except for the initial 24 hours of a slight increase in corrosion rate.…”
Section: Electrochemical Test (Potentiodynamic Polarization Test)supporting
confidence: 74%
“…After 2 days, AZ91 was corroded on some parts of its surface and its material loss increased gradually as shown in figure 5.7. The corrosion morphology of AZ91 in 3.5% NaCl was similar to the morphology caused by 5% NaCl reported in [147]. Raman et al [30] described that the die cast AZ91D showed a steady decrease in corrosion rate up to 6 days, except for the initial 24 hours of a slight increase in corrosion rate.…”
Section: Electrochemical Test (Potentiodynamic Polarization Test)supporting
confidence: 74%
“…2. The corrosion potential on the forward scan is −1.564 V and that on the reverse scan is −1.579 V. The corrosion potential on the reverse scan is more negative than the forward scan, which indicates that corroded area still acts as anode for further galvanic corrosion and protects the non-corroded area as cathode, resulting in accelerated corrosion in the corroded area, causing the formation of pits [47]. The formation of visible pits on the surface of the alloy is as shown in Fig.…”
Section: Cyclic Polarizationmentioning
confidence: 93%
“…Apesar da textura cristalográfica explicar relativamente a corrosão da liga AZ31, não explora a interferência do tamanho de grão. Zhang et al [17] sugeriu que contornos de grão atuam facilitando a passivação reduzindo a taxa de corrosão. Outro estudo [20] indicou ainda que uma possível alternativa para reduzir a taxa de corrosão é reduzir o tamanho de grão.…”
Section: Curvas De Polarizaçãounclassified